2015
DOI: 10.18632/oncotarget.4640
|View full text |Cite
|
Sign up to set email alerts
|

Glioma-derived plasminogen activator inhibitor-1 (PAI-1) regulates the recruitment of LRP1 positive mast cells

Abstract: Glioblastoma (GBM) is a high-grade glioma with a complex microenvironment, including various inflammatory cells and mast cells (MCs) as one of them. Previously we had identified glioma grade-dependent MC recruitment. In the present study we investigated the role of plasminogen activator inhibitor 1 (PAI-1) in MC recruitment.PAI-1, a primary regulator in the fibrinolytic cascade is capable of forming a complex with fibrinolytic system proteins together with low-density lipoprotein receptor-related protein 1 (LR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…proliferative and mesenchymal genes). Interestingly, some of the validated ZBTB18 targets have been previously associated with unfavorable prognosis in glioma [25-27]. Further examination of the top downregulated genes by ZBTB18 in JX6 cells by gene expression array highlighted many genes previously reported to play a role in epithelial-to-mesenchymal transition (EMT) (Figure 3A) [28-34].…”
Section: Resultsmentioning
confidence: 99%
“…proliferative and mesenchymal genes). Interestingly, some of the validated ZBTB18 targets have been previously associated with unfavorable prognosis in glioma [25-27]. Further examination of the top downregulated genes by ZBTB18 in JX6 cells by gene expression array highlighted many genes previously reported to play a role in epithelial-to-mesenchymal transition (EMT) (Figure 3A) [28-34].…”
Section: Resultsmentioning
confidence: 99%
“…Seven genes (CSF1, EIF4EBP1, ESM1, IGFBP1, LPL, SERPINE1 and TP53) that were reported to be downregulated by LGI3 may be upregulated in glioma due to the downregulation of LGI3. In particular, CSF1, EIF4EBP1, SERPINE1 and TP53 (p53) were postulated to be functionally involved in glioma 22,30,32,33. Thus, we hypothesize that LGI3 downregulation in glioma may account for downregulation in glioma of the genes that were shown to be upregulated by LGI3 (IGF1 and PTGS2) and upregulation of the genes that were shown to be downregulated by LGI3 (CSF1, EIF4EBP1, ESM1, IGFBP1, LPL, SERPINE1 and TP53).…”
Section: Discussionmentioning
confidence: 96%
“…Previous investigations have demonstrated that overexpression of SERPINE1 in GBM is associated with shorter survival and its serum levels were shown to be predictive for glioma grade . Roy et al studied the role of SERPINE1 on the mast cells recruitment in gliomas. Deepak suggested heterogeneous activation of TGFβ and increased SERPINE1 expression in GBM .…”
Section: Discussionmentioning
confidence: 99%